Asset protection through security awareness - Speed, Tyler Justin (Boca Raton, Fla. : CRC Press, 2012)
"Supplying a high-level overview of how to protect your company's physical and intangible assets, Asset Protection through Security Awareness explains the best ways to enlist the assistance of your employees as the first line of defense in safeguarding company assets and mitigating security risks. It reviews key topics surrounding computer security--including privacy, access controls, and risk management--to help you fill the gaps that might exist between management and the technicians securing your network systems. Requiring no previous networking or programming experience, the book delivers a practical approach to asset protection. It specifies the roles of managers and employees in creating a company-wide culture of security awareness and provides step-by-step instruction on how to build an effective security awareness team. Each chapter examines a separate security issue and provides a brief overview of how to address that issue. This book includes helpful tools and checklists to help you address: - Visual, digital, and auditory data security - Payment card industry (PCI) compliance, password management, and social engineering - User authentication methods - Computer and network forensics - Physical security and continuity planning - Privacy concerns and privacy-related regulation This concise security management primer facilitates the up-to-date understanding required to protect your digital and physical assets, including customer data, networking equipment, and employee information. Providing you with powerful tools of diplomacy, this text will help you win the support of your employees and empower them to be effective gatekeepers of your company's most valued assets and trade secrets. "--
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Computer networks -- Security measures; Information technology -- Security measures; Business enterprises -- Security measures; Electronic books